Increasing Understanding of One-Way ANOVA Material for Accounting Students: A Case Study of Deposit Interest - Intan Purnama (First Ciera Publisher, 2023)
This study aims to increase accounting students' understanding of one-way ANOVA. This study uses a simple example of deposit interest from several national banks to facilitate analysis. This study used one-way analysis of variance (ANOVA) which was used to analyze differences in means between groups and related procedures. The results showed that the calculated F value > F table, which means the hypothesis is accepted. It is true that there are significant differences in deposit interest rates between Bank Anz Indonesia, Bank Bukopin, Bank Central Asia, and Bank Cimb Niaga. Understanding this material is important and relevant to the world of accounting and finance. It is hoped that this research can become a basis for further research and educational development efforts in strengthening statistical understanding among accounting students.